Landing Constraints Influence Ground Reaction Forces and Lower Extremity EMG in Female Volleyball Players - Tillman, M. D.; Criss, R. M.; Brunt, D.; Hass, C. J. (Journal of Applied Biomechanics, 2004)
The purposes of this study were to analyze double-limb, dominant-limb, and nondominant-limb landings, each with a two-footed takeoff, in order to detect potential differences in muscle activity and ground reaction forces and to examine the possible influence of leg dominance on these parameters. Each of the three jump landing combinations was analyzed in 11 healthy female volleyball players (age 21 ± 3 yrs; height 171 ± 5 cm, mass 61.6 ± 5.5 kg, max. vertical jump height 28 ± 4 cm). Ground reaction forces under each limb and bilateral muscle activity of the vastus medialis, hamstrings, and lateral gastrocnemius muscles were synchronized and collected at 1,000 Hz. Normalized EMG amplitude and force platform data were averaged over five trials for each participant and analyzed using repeated-measures ANOVA. During the takeoff phase in jumps with one-footed landings, the non-landing limb loaded more than the landing limb (p = 0.003). During the 100 ms prior to initial contact, single-footed landings generated higher EMG values than two-footed landings (p = 0.004). One-footed landings resulted in higher peak vertical loading, lateral loading, and rate of lateral loading than two-footed landings (p < 0.05). Trends were observed indicating that muscle activation during one-footed landings is greater than for two-footed landings (p = 0.053 vs. p = 0.077). The greater forces and rate of loading produced during single-limb landings implies a higher predisposition to injury. It appears that strategic planning and training of jumps in volleyball and other jumping sports is critical.